2012
DOI: 10.2341/11-365-l
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Outgassing, Tear Strength, and Detail Reproduction in Alginate Substitute Materials

Abstract: Alginate substitute materials are inexpensive polyvinyl siloxane (PVS) impression materials that exhibit better detail reproduction and tear strength than alginate. Alginate substitute materials do show slightly more outgassing and resulting cast porosity than traditional alginates, particularly when they are poured soon after mixing. To reduce cast surface porosity, a minimum pouring delay of 60 minutes is suggested. SUMMARYObjective: To compare three alginate substitute materials to an alginate impression ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
1
3
1
Order By: Relevance
“…The present study found in both groups, the percentages of deviations and the absolute changes (in µm) from typodont model for PVS impression material were less compared to those of alginate substitute impression material however, the differences were not statistically significant. This finding supported the dimensional stability of alginate substitute impression material that was reported by Baxter et al [28] Although, the PVS still the material of choice for multiunit implant restoration according the recommendation of Schmidt et al (2018), who reported that the impression material had the greatest effect on the impression accuracy and recommended the polyvinyl siloxane impression materials for multiunit restoration supported by non-parallel dental implants. [34] In contrast to previous findings, researchers found that, the PVS was not superior to other irreversible hydrocolloid materials if splinted impression coping technique was used for impression of multiunit implant restoration.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The present study found in both groups, the percentages of deviations and the absolute changes (in µm) from typodont model for PVS impression material were less compared to those of alginate substitute impression material however, the differences were not statistically significant. This finding supported the dimensional stability of alginate substitute impression material that was reported by Baxter et al [28] Although, the PVS still the material of choice for multiunit implant restoration according the recommendation of Schmidt et al (2018), who reported that the impression material had the greatest effect on the impression accuracy and recommended the polyvinyl siloxane impression materials for multiunit restoration supported by non-parallel dental implants. [34] In contrast to previous findings, researchers found that, the PVS was not superior to other irreversible hydrocolloid materials if splinted impression coping technique was used for impression of multiunit implant restoration.…”
Section: Discussionsupporting
confidence: 84%
“…These impression materials have been reported to offer improved detail reproduction, tear strength, and dimensional stability. [28] In the present study, it was found that there was no statistical significance difference between the open and closed tray impression techniques using the monophase PVS material. This is in agreement with the findings of Osman et al and Wenz et al [29,30] In contrast, Daoudi et al and AlQuran et al found that the open tray impression technique was more accurate and significantly superior to closed tray impression technique.…”
Section: Discussioncontrasting
confidence: 41%
“…Alginate substitutes. These substances have better mechanical properties than conventional alginate [11]. Alginate substitutes are of a lower cost than traditional PVS, but more expensive than alginate.…”
Section: Alginatesmentioning
confidence: 99%
“…Recent studies have reported that these two irreversible hydrocolloid alternatives were more accurate with regard to the surface detail reproduction and they were dimensionally stable over an extended period. [ 26 27 28 29 ] However, the number of laboratory and clinical investigations on these materials is much lower than the number of studies on traditional irreversible hydrocolloids.…”
Section: Introductionmentioning
confidence: 99%